Rāingān kānsamrūat radap prathēt rư̄ang phonkrathop čhāk nayōbāi khūapkhum kānbō̜riphōk yāsūp nai Prathēt Thai : klum wairun rō̜p thī 5 (Phō̜. Sō̜. 2554) phāitai Khrōngkān International Tobacco Control Policy-Southeast Asia - Thawimā Siriratsamī (ʻĒkkasān thāng wichākān / Sathāban Wičhai Prachākō̜n læ Sangkhom, Mahāwitthayālai Mahidon ;, 2013)
International Tobacco Control Policy Survey on tabacco use of teenagers and protection in Thailand conducted in 2011.